1981
DOI: 10.1152/ajpheart.1981.241.4.h557
|View full text |Cite
|
Sign up to set email alerts
|

Length-dependent sensitivity in vascular smooth muscle

Abstract: Dose-response curves were obtained from dog anterior tibial artery rings at various lengths (L) to determine whether sensitivity to norepinephrine (NE) and potassium (K+) depends on arterial circumference. The dose for half maximal response (ED50) was determined by graphical estimation and by calculation from a best fit curve. For both NE and K+: 1) ED50 was lowest (most sensitive) at L for maximum active force (Lmax) and increased significantly as L decreased from Lmax; 2) ED50 at 1.0 and 1.15 Lmax was not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
44
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 0 publications
9
44
0
Order By: Relevance
“…The alteration of wall tension may activate or inactivate the contraction of vascular smooth muscle and the signal pathways of endothelial cells mediated by mechanotransductions such as integrins and G protein-coupled receptors (9, 17, 25, 26). It has been suggested that the change in distension or stretch affects vascular reactivity (3,6,22,27). In the present study, we extended the pressure and stretch to a pathological range (e.g., hypertensive pressures or stretches) and verified that the effect on the vasorelaxation of blood vessel is substantial (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The alteration of wall tension may activate or inactivate the contraction of vascular smooth muscle and the signal pathways of endothelial cells mediated by mechanotransductions such as integrins and G protein-coupled receptors (9, 17, 25, 26). It has been suggested that the change in distension or stretch affects vascular reactivity (3,6,22,27). In the present study, we extended the pressure and stretch to a pathological range (e.g., hypertensive pressures or stretches) and verified that the effect on the vasorelaxation of blood vessel is substantial (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…However, force development induced by U-46619 in Ca2+- sensitivity for vasocontraction of a longer muscle, as observed by Price et al (1981), is not necessarily associated with increases in [Ca2+]i, but can be explained by a further potentiation of Ca2+ sensitivity of contractile apparatus during agonist stimulation by stretch, as evidenced by the present study (Fig. 6D) (Chatterjee & Murphy, 1983;Moreland & Murphy, 1986) and co-operative cycling of cross-bridges ).…”
Section: Methodssupporting
confidence: 62%
“…Thus, the optimal tension determined in vitro is in the range of physiological wall tension. Affinity of adrenergic receptors in arterial smooth muscle is influenced by alterations in wall tension (Raffa and Tallarida, 1981;Price et al, 1981).…”
Section: Discussionmentioning
confidence: 99%